Government Interventions Driving Indonesia’s Global Electric Vehicle Battery Production - Lestaluhu, Fitri Alfiani; Darwis, Danial (Institut Agama Islam Negeri Kerinci, 2024)
The demand for energy is increasing in this technological era. However, the supply of natural energy resources is decreasing. The establishment of Indonesia Battery Corporation (IBC) aims not only to meet the public's energy needs by utilizing batteries as a source of energy but also to contribute to Indonesia's economic development. This initiative serves as a catalyst for Indonesia in the development of battery energy. The purpose of this research is to examine the government's interest in enhancing Indonesia's economy through energy transition, using mercantilist economic theory to explain government intervention. The research method employed by the author is a qualitative method, utilizing secondary data from various sources such as journal articles, books, websites, and other sources. Data collection techniques involve literature study, and the data is then analyzed using qualitative data analysis techniques. The findings of this research indicate the importance of government intervention in the production process of batteries as energy sources for global electric vehicles, which can enhance Indonesia's economy and promote Indonesia's position as a strong country in the global electric vehicle battery production market.